River water quality issues in Malaysia - Nor Azura, Che Mahmud (2021)
Rapid urbanisation and population growth have contributed both to an ever-increasing demand for water consumption and, at the same time, to the level of water pollution in Malaysia. The quality of water in Malaysia, as well as access to water in general, is a major concern. Lakes and reservoirs act as domestic, commercial, agricultural, hydroelectric, navigational, and recreational water resources. As 98% of water comes from rivers (Chan, 2012), rivers’ pollution is a real problem with more and more rivers are polluted.